Desenvolvimento de um modelo de previsão de fósforo para o convertedor LD da V&M do Brasil - Leandro Peixoto Almeida (2005)
To meet the increasing demand for low phosphorus steels at competitive costs, V&M Brazil invested on the optimization of its BOF steelmaking process. At V&M Brazil, dephosphorisation is mainly developed at the BOF shop. Phosphorus removal is a metal-slag reaction. To achieve high levels of dephosphorisation, anoxidant atmosphere with intense agitation is required. Slag composition also had a significant effect on phosphorus partition between slag and metal. In the present work, a model to evaluate the phosphorus partition has been developed based on industrial data obtained from the V&M BOF. The model indicated that the variables that have a more significant effect on the phosphorus partition are CaO, MgO and Fe contents of the slag and steel temperature at the end of the blow. The partition model was used in the prediction of the phosphorus content of the steel atthe end of the blow. The predictions of the model were in reasonable agreement with the experimental data, when provided precise information on the total phosphorus input and on slag composition, especially Fe, CaO and MgO contents, can be obtained. The results also pointed out that to attain higher levels of reliability of the predictions, further improvements in the quality of the data used in the model are required.